Olive oil biophenols and women’s health - Ivan Fistonić; Mario Harapin; Nikola Fistonić; Vedrana Bulat; Mirna Šitum; Donatella Verbanac (Medicinski Glasnik, 2012)
Olea europea, the olive tree, is an ancient tree that originates fromthe Mediterranean environment of Asia Minor. The edible olive fruit is also used for its oil, gained by the process of pressing, a nutrient with proven beneficial effects. Virgin olive oil is the natural juice of the olive fruit, which plays a major role in the healthy Mediterranean diet. The source of its health effects are the biophenols and squalenes (oleocanthal, tyrosol, hydroxytyrosol, oleuropein) it contains. They provide an exceptional antioxidative activity, removing harmful compounds from the body. Oxidants are essential in the genesis of many diseases and conditions, such as cardiovascular disorders, cancer, osteoporosis, Alzheimer disease, andpremenstrual syndrome. Oleic acid, an unsaturated fatty acid, has demonstrated a significant effect in the prevention of malignant diseases such as colon cancer and breast cancer. Biophenols from olive oil successfully suppress the synthesis of LDL, a protein that is crucial in the development of cardiovascular disease, by reducingblood pressure and the development of atherosclerotic plaques. In addition, there is strong evidence of the antimicrobic effect of the biphenols from olive oil that successfully destroy colonies of microorganisms which may cause respiratory tract, intestinal,and genital tract infections.